2001
DOI: 10.1002/jemt.1137
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical study of Streptococcus agalactiae and macrophage interaction

Abstract: Light and electron microscopy were used to analyse the process of interaction of Streptococcus agalactiae (serotypes Ia, III, and V) with resident and activated mouse peritoneal macrophages. Transmission electron microscopy showed that adherence of the S. agalactiae serotype Ia, but not III and V serotypes, to the surface of activated macrophages triggers the respiratory oxidative burst as revealed by the presence of reduced nicotinamide adenine dinucleotide (phosphate) [NAD(P)H]-oxidase in the phagocytic vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…GBS serotypes III (80340-vagina carrier and 90356-cerebrospinal fluid [CSF] clinical isolate) and V (88641-vagina carrier and 90186-blood clinical isolate) partially investigated for adhesive properties (10,11) were used in this study. The strains obtained from Culture Collection of the Laboratório de Cocos Patogênicos, Departamento de Microbiologia Médica, Instituto de Microbiologia Professor Paulo de Góes, Universidade Federal do Rio de Janeiro, Brazil, were identified as group B and serotyped as described previously (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GBS serotypes III (80340-vagina carrier and 90356-cerebrospinal fluid [CSF] clinical isolate) and V (88641-vagina carrier and 90186-blood clinical isolate) partially investigated for adhesive properties (10,11) were used in this study. The strains obtained from Culture Collection of the Laboratório de Cocos Patogênicos, Departamento de Microbiologia Médica, Instituto de Microbiologia Professor Paulo de Góes, Universidade Federal do Rio de Janeiro, Brazil, were identified as group B and serotyped as described previously (12).…”
Section: Methodsmentioning
confidence: 99%
“…Glutathione S-transferases (GST) are ubiquitous proteins whose primary function is related to detoxification of endo-and exogenous toxic molecules, thus protecting cells from oxidative stress (34,35). Previous studies demonstrated that GBS is capable of triggering oxidative burst in mammalian cells (11,36). The increase of the expression of GST in HUVECs under interaction with GBS might represent a protective mechanism displayed by endothelial cells to protect them against oxidative molecules generated or activated during such cell-bacterium interaction, but more experiments are necessary.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Subsequently, infected HUVECs were washed and treated with 200 μl M199 with orange acridine, re-incubated for 20 min at 37˚C/5% CO 2 and washed with M199 without orange acridine. The presence of orangestained GBS was considered indicative of the GBS-containing vacuole acidification (confocal laser scanning microscopy (CLSM Zeiss 310) (12).…”
Section: Gbs -Cfu Intracellular Gbs] (9)mentioning
confidence: 99%
“…Monolayers were post-fixed with 1% OsO 4 , 5 mM CaCl 2 and 0.8% K 4 [Fe(CN 6 )] in cacodylate buffer for 1 h at 22˚C, and dehydrated through a series of graded ethanol solutions and embedded in Epon. Ultra-thin sections were examined under Zeiss EM 906 transmission electron microscope (Zeiss, Oberkochen, Germany) (20).…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%